2020
DOI: 10.1155/2020/6853176
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Design Guidelines for Hot‐Rolled I‐Shaped Steel Compression Members according to AISC 360‐16 and EC3

Abstract: Thirty-six years after its publication, Turkish Building Code for Steel Structures was replaced with a more rational specification, Specification of Design and Construction of Steel Structures (SDCSS), which was prepared almost entirely based on the current American steel design specification (AISC 360-16). European steel design specification (EC3) is also widely used in Turkey for the design of steel structures constructed with the collaboration of Turkish and European companies. It is essential for a steel d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…An analogous procedure has been used to draw the results with CSA S16-19 [105] and AISC360-16 [106] that adopt a resistance factor of 0.90 [107], overestimating 90 and 96 outcomes. Similarly, the GB50017-2017 standard [79] overestimates 104 results, with 𝛼 1 , 𝛼 2 , and 𝛼 3 of 0.65, 0.965, and 0.3.…”
Section: Initial Imperfectionmentioning
confidence: 99%
“…An analogous procedure has been used to draw the results with CSA S16-19 [105] and AISC360-16 [106] that adopt a resistance factor of 0.90 [107], overestimating 90 and 96 outcomes. Similarly, the GB50017-2017 standard [79] overestimates 104 results, with 𝛼 1 , 𝛼 2 , and 𝛼 3 of 0.65, 0.965, and 0.3.…”
Section: Initial Imperfectionmentioning
confidence: 99%
“…Naseri et al (2020) presented an experimental study into the buckling behavior of Glass Fabric-Reinforced Polymer (GFRP) cylindrical shells subjected to axial compression load. Pinarbasi et al (2020) dealt with the Turkish Building Code for Steel Structures replaced with a more rational Specification of Design and Construction of Steel Structures (SDCSS), which was prepared based on the American steel design specification (AISC 360-16). Qays and Al-Zuhairi (2020) discussed the idea of using slender Reinforced Concrete (RC) columns with crossshaped (+-shaped) instead of square-shaped columns.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…It was concluded that the GFRP cylindrical shells showed the full-buckling strength and had local buckling failure mode. Pinarbasi et al (2020) dealt with the Turkish Building Code for Steel Structures replaced with a more rational Specification of Design and Construction of Steel Structures (SDCSS), which was prepared based on the American steel design specification (AISC 360-16). European steel design specification (EC3) was also widely used in Turkey.…”
Section: Introductionmentioning
confidence: 99%